2015
DOI: 10.1590/0004-282x20150189
|View full text |Cite
|
Sign up to set email alerts
|

Survival score scales of patients operated with spinal metastases: retrospective application in a Brazilian population

Abstract: Spinal cord epidural metastasis (SEM) is a common complication of systemic cancer. Predicting these patient’s survival is a key factor to select the proper treatment modality, but the three most used score scales to predict their survival (Tokuhashi revised score, Tomita score and Bauer modified score) were designed in single institutions and their reliability to predict correctly the patient’s survival were first tested only in those specific populations. This prognostication issue is addressed in this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The median OS of our patients was 8.4 months, similar to previous reports of medians of 6–14 months. [ 6 10 11 12 13 14 15 16 ] For instance, the study by Van der Linden et al by the Dutch Bone Metastasis Study Group[ 17 ] reported a 7-month OS. Age, KPS, ECOG, and the presence of extraspinal metastases considered unresectable were characteristics associated with survival in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The median OS of our patients was 8.4 months, similar to previous reports of medians of 6–14 months. [ 6 10 11 12 13 14 15 16 ] For instance, the study by Van der Linden et al by the Dutch Bone Metastasis Study Group[ 17 ] reported a 7-month OS. Age, KPS, ECOG, and the presence of extraspinal metastases considered unresectable were characteristics associated with survival in our cohort.…”
Section: Discussionmentioning
confidence: 99%